2019
DOI: 10.1007/s00417-019-04464-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of diabetic macular edema and factors predicting outcomes in sham-treated patients (MEAD study)

Abstract: Purpose To describe the natural history of diabetic macular edema (DME) with respect to best-corrected visual acuity (BCVA) and central retinal thickness (CRT) outcomes and to identify baseline patient characteristics and systemic factors associated with improvement or worsening of outcomes in sham-treated patients. Methods The study population was sham-treated patients (n = 350) in the 3-year MEAD registration study of dexamethasone intravitreal implant for treatment of DME. Patients had center-involved DME a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Our results are consistent with the natural history findings of 350 patients with DME in the MEAD study, where older age and worse baseline DR severity scores were associated with worse BCVA outcomes. 27 We also confirmed the findings from a post-hoc analysis of Protocol V, where observed eyes with worse DR severity were also more likely to require antivascular endothelial growth factor treatment during the 2 years study. 16 Although some studies suggest that HbA1c could be used to stratify the monitoring frequency of untreated DME, with eyes with HbA1c ≥8.5% being 5.7 times more likely to develop CST thickening, 28 neither our study or Protocol V found HbA1c to be a useful predictor of vision loss.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results are consistent with the natural history findings of 350 patients with DME in the MEAD study, where older age and worse baseline DR severity scores were associated with worse BCVA outcomes. 27 We also confirmed the findings from a post-hoc analysis of Protocol V, where observed eyes with worse DR severity were also more likely to require antivascular endothelial growth factor treatment during the 2 years study. 16 Although some studies suggest that HbA1c could be used to stratify the monitoring frequency of untreated DME, with eyes with HbA1c ≥8.5% being 5.7 times more likely to develop CST thickening, 28 neither our study or Protocol V found HbA1c to be a useful predictor of vision loss.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we followed the natural history of 48 patients with treatment-naïve DME and good baseline visual acuity (Snellen equivalent of 20/25 or better) similar to those from DRCR Protocol V's observation arm, and analyzed various baseline clinical and anatomic characteristics that may predict greater risk for a vision loss event, defined as visual acuity loss of $2 Snellen lines at any visit or 1 to 2 lines at two consecutive visits, based on the threshold for initiating aflibercept therapy in Protocol V. We found that the clinical factors most strongly associated with vision 27 We also confirmed the findings from a post-hoc analysis of Protocol V, where observed eyes with worse DR severity were also more likely to require antivascular endothelial growth factor treatment during the 2 years study. 16 Although some studies suggest that HbA1c could be used to stratify the monitoring frequency of untreated DME, with eyes with HbA1c $8.5% being 5.7 times more likely to develop CST thickening, 28 neither our study or Protocol V found HbA1c to be a useful predictor of vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when dividing the patients into three categories based on the number of letters lost (0–5, 5–10, >10), no significant difference was found between the 2 years. These results consist of long-term studies such as the MEAD and VISION [ 23 , 24 ] and can be attributed to the undertreatment in real life or to the progression of the disease despite treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A post-hoc analysis of sham-treated eyes in the MEAD study revealed a significantly better 3-year result in eyes without prior hypertension (difference: +5.8 letters). Furthermore, anatomically better results were found in eyes with anti-hypertensive therapy [ 22 ], suggesting a positive effect of anti-hypertensive treatment on edema reduction.…”
Section: Discussionmentioning
confidence: 99%